Software requirements engineering (IEEE Computer Society Press, 2000)
This new edition describes current best practices in requirements engineering with a focus primarily on software systems but also on systems that may contain other elements such as hardware or people. The text consists of original papers, written by experts in the field, plus revisions of papers from the first edition. The book begins with an introduction to current issues and the basic terminology of the software requirements engineering process.